Copolyester material as well as preparation method and application thereof
By designing the molecular structure of the copolyester material, using 2,6-naphthalene dicarboxylic acid and 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, combined with composite stabilizers and catalysts, copolyester materials with excellent thermal performance, cooking resistance, optical performance and gas barrier properties were prepared, solving the problem of insufficient performance of existing materials in high-heat scenarios.
Patent Information
- Application Number
- CN202510223597.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-27
AI Technical Summary
When used in high-thermal scenarios, the thermal performance, cooking resistance, optical performance and gas barrier properties are insufficient, making it difficult to meet the needs of high-temperature cooking food packaging bags.
By designing the molecular structure of the copolyester material, copolyester materials with excellent thermal properties, cooking resistance, optical properties and gas barrier properties were prepared using 70-98 mol% of 2,6-naphthalene dicarboxylic acid residues and 10-60 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, combined with a composite stabilizer and a catalyst, transesterification and polycondensation reaction were carried out to prepare copolyester materials with excellent thermal properties, cooking resistance, optical properties and gas barrier properties.
It realizes excellent performance of copolyester materials in high heat scenarios of 100-135℃, has high glass transition temperature, low oxygen transmission, good light transmittance and haze, and is suitable for high-temperature resistant cooking food packaging bags.
Smart Images

Figure CN119912670A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of engineering plastics, and specifically relates to a copolyester material and a preparation method and application thereof. Background Art
[0002] Poly(1,4-cyclohexanedimethanol-co-2,2,4,4-tetramethyl-1,3-cyclobutanediol terephthalate) (abbreviated as PCcBT, trade name TritanTM) is a high-performance copolyester material developed by Eastman Corporation of the United States based on 1,4-cyclohexanedimethanol (CHDM), dimethyl terephthalate (DMT) and the large steric monomer 2,2,4,4-tetramethyl-1,3-cyclobutanediol (CBDO). It has the characteristics of high heat resistance (glass transition temperature>90℃), high light transmittance (transmittance>90%), high toughness and does not contain bisphenol A. It has been widely used in food packaging, cosmetic packaging, medical packaging and other fields.
[0003] At present, PCcBT mainly adjusts the thermal properties of copolyester materials through the ratio of CHDM and CBDO. Specifically, increasing the ratio of CBDO in the formula can significantly increase the glass transition temperature (Tg) of polyester. Although the homopolyester composed of CBDO and terephthalic acid has a Tg higher than 180°C, since CBDO is a high-steric primary diol, the polymerization activity of hydroxyl is low. When the proportion of CBDO in diol exceeds 40 mol%, it is difficult to obtain a resin with a viscosity > 0.6 dL / g. The glass transition temperature of high-viscosity copolyester materials is difficult to exceed 125°C, that is, it is difficult to have both high heat resistance and high molecular weight at the same time; in addition, PCcBT has insufficient gas barrier capacity, which is limited when used in food packaging materials. The above limits the use of this type of material in high-temperature scenarios such as high-temperature cooking food packaging bags.
[0004] Therefore, there is an urgent need to provide a copolyester material with excellent thermal properties, cooking resistance, optical properties and gas barrier properties. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a copolyester material and a preparation method and application thereof. The copolyester material provided by the present invention can simultaneously have excellent thermal properties, cooking resistance, optical properties and gas barrier properties by designing the molecular structure of the copolyester contained therein, and can meet the application requirements in high-temperature scenarios such as high-temperature cooking-resistant food packaging bags (temperature resistant 100-135°C).
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a copolyester material, wherein the components of the copolyester material include copolyester; the copolyester contains dibasic acid residues and diol residues.
[0008] The dibasic acid residue comprises:
[0009] (a1) 70-98 mol % of 2,6-naphthalene dicarboxylic acid residues, based on the total molar amount of (a1) and (a2);
[0010] (a2) 2-30 mol % of other dibasic acid residues based on the total molar amount of (a1) and (a2);
[0011] wherein the sum of the molar percentages of residues (a1) and (a2) is 100%;
[0012] The diol residue comprises:
[0013] (b1) 10 to 60 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, based on the total molar amount of (b1) and (b2);
[0014] (b2) 40 to 90 mol % of other diol residues, based on the total molar amount of (b1) and (b2);
[0015] The total molar percentage of the residues (b1) and (b2) is 100%.
[0016] The copolyester material provided by the present invention can simultaneously have excellent thermal properties, boiling resistance, optical properties and gas barrier properties by designing the molecular structure of the copolyester contained therein; wherein the residue (a1) in the molecular structure of the copolyester has a naphthalene ring structure with strong rigidity, and the interaction between molecules is more significant, which can significantly improve the heat resistance and gas barrier properties of the copolyester material and is more conducive to the preparation of heat-resistant and high-barrier copolyester materials.
[0017] Preferably, the mass percentage of copolyester in the copolyester material is 97.5-99.99%, for example, it can be 97.6%, 97.8%, 98%, 98.2%, 98.4%, 98.6%, 98.8%, 99%, 99.2%, 99.4%, 99.6%, 99.8%, 99.9%, etc., and more preferably 98-99.6%.
[0018] The molar percentage of 2,6-naphthalene dicarboxylic acid residues in the dibasic acid residues is 70-98 mol%, for example, it can be 72 mol%, 74 mol%, 76 mol%, 78 mol%, 80 mol%, 82 mol%, 84 mol%, 86 mol%, 88 mol%, 90 mol%, 92 mol%, 94 mol%, 96 mol%, etc.
[0019] The molar percentage of other dibasic acid residues in the dibasic acid residue is 2-30 mol%, for example, it can be 4 mol%, 6 mol%, 8 mol%, 10 mol%, 12 mol%, 14 mol%, 16 mol%, 18 mol%, 20 mol%, 22 mol%, 24 mol%, 26 mol%, 28 mol% and the like.
[0020] The molar percentage of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues in the diol residues is 10-60 mol%, for example, it can be 12 mol%, 15 mol%, 18 mol%, 20 mol%, 22 mol%, 24 mol%, 26 mol%, 28 mol%, 30 mol%, 32 mol%, 35 mol%, 38 mol%, 40 mol%, 42 mol%, 45 mol%, 48 mol%, 50 mol%, 52 mol%, 55 mol%, 58 mol% and the like.
[0021] The molar percentage of other diol residues in the diol residue is 40-90 mol%, for example, it can be 42 mol%, 45 mol%, 48 mol%, 50 mol%, 52 mol%, 55 mol%, 58 mol%, 60 mol%, 62 mol%, 65 mol%, 68 mol%, 70 mol%, 72 mol%, 75 mol%, 78 mol%, 80 mol%, 82 mol%, 85 mol%, 88 mol% and the like.
[0022] In the present invention, the other dibasic acid residue is a dibasic acid residue different from the 2,6-naphthalene dicarboxylic acid residue.
[0023] In the present invention, the other diol residue is a diol residue different from the 2,2,4,4-tetramethyl-1,3-cyclobutanediol residue.
[0024] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0025] As a preferred technical solution, the other dibasic acid residues include any one of terephthalic acid residues, furandicarboxylic acid residues, 4,4-biphenyldicarboxylic acid residues, 1,3-isophthalic acid residues or phthalic acid residues, or a combination of at least two thereof.
[0026] Preferably, the dibasic acid residue comprises:
[0027] (a1) 75-95 mol % of 2,6-naphthalene dicarboxylic acid residues, based on the total molar amount of (a1) and (a2);
[0028] (a2) 5-25 mol % of other dibasic acid residues based on the total molar amount of (a1) and (a2);
[0029] The total molar percentage of the residues (a1) and (a2) is 100%.
[0030] The molar percentage of 2,6-naphthalene dicarboxylic acid residues in the dibasic acid residues is 75-95 mol%, for example, it can be 77 mol%, 79 mol%, 81 mol%, 83 mol%, 85 mol%, 87 mol%, 89 mol%, 91 mol%, 93 mol%, etc.
[0031] The molar percentage of other dibasic acid residues in the dibasic acid residue is 5-25 mol%, for example, it can be 7 mol%, 9 mol%, 11 mol%, 13 mol%, 15 mol%, 17 mol%, 19 mol%, 21 mol%, 23 mol%, etc.
[0032] Preferably, the other diol residues include any one of 1,4-cyclohexanedimethanol residues, 1,4-cyclohexanediol residues, 1,2-cyclohexanedimethanol residues, 1,3-cyclohexanediol residues, 1,2-cyclohexanediol residues, 1,3-cyclohexanediol residues, ethylene glycol residues, 1,3-propylene glycol residues, 1,4-butanediol residues, dicyclopentanediol residues, neopentyl glycol residues or 2-methyl-1,3-propanediol residues, or a combination of at least two thereof.
[0033] Preferably, the diol residue comprises:
[0034] (b1) 25 to 50 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, based on the total molar amount of (b1) and (b2);
[0035] (b2) 50-75 mol % of other diol residues, based on the total molar amount of (b1) and (b2);
[0036] The total molar percentage of the residues (b1) and (b2) is 100%.
[0037] The molar percentage of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues in the diol residues is 25-50 mol%, for example, it can be 26 mol%, 29 mol%, 31 mol%, 33 mol%, 34 mol%, 37 mol%, 39 mol%, 41 mol%, 43 mol%, 44 mol%, 46 mol%, 47 mol%, 49 mol%, etc.
[0038] The molar percentage of other diol residues in the diol residue is 50-75 mol%, for example, it can be 51 mol%, 53 mol%, 54 mol%, 56 mol%, 57 mol%, 59 mol%, 61 mol%, 63 mol%, 64 mol%, 66 mol%, 67 mol%, 69 mol%, 70 mol%, 71 mol%, 72 mol%, 73 mol%, 74 mol% and the like.
[0039] Preferably, the components of the copolyester material further include a composite stabilizer.
[0040] Preferably, the composite stabilizer includes a phosphorus stabilizer and a hindered phenol stabilizer.
[0041] Preferably, the phosphorus-based stabilizer includes any one of diphenyl phosphate, triphenyl phosphite, trimethyl phosphate, dimethyl phosphate, triphenyl phosphate, diphenyl phosphite, ammonium phosphite, diammonium phosphate, phosphorous acid, hypophosphorous acid, pyrophosphoric acid, tris(2,4-di-tert-butylphenyl) phosphite or ammonium phosphate, or a combination of at least two thereof.
[0042] Preferably, the mass percentage of the phosphorus stabilizer in the composite stabilizer is 10-90%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc., and more preferably 45-75%.
[0043] Preferably, the hindered phenol stabilizer includes any one or a combination of at least two of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester (antioxidant 1010), 2,4-dimethyl-6-(1-methylpentadecyl)-phenol (antioxidant 1076), N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (antioxidant 1098) or 2,6-di-tert-butyl-4-methylphenol.
[0044] Preferably, the mass percentage of the hindered phenol stabilizer in the composite stabilizer is 10-90%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc., and more preferably 25-55%.
[0045] Preferably, the mass percentage of the composite stabilizer in the copolyester material is 0.01-1%, for example, it can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95% and the like.
[0046] Preferably, the components of the copolyester material further include a catalyst.
[0047] Preferably, the catalyst includes any one of a tin-based catalyst, an antimony-based catalyst, a germanium-based catalyst, a titanium-based catalyst or an aluminum-based catalyst, or a combination of at least two thereof.
[0048] Preferably, the tin-based catalyst includes any one of dibutyltin oxide, stannous isooctanoate, monobutyltin triisooctoate or dioctyltin oxide, or a combination of at least two thereof.
[0049] Preferably, the antimony-based catalyst includes any one of antimony acetate, antimony trioxide, ethylene glycol antimony or polyethylene glycol antimony, or a combination of at least two of them.
[0050] Preferably, the germanium-based catalyst includes germanium dioxide and / or germanium oxide.
[0051] Preferably, the titanium-based catalyst includes any one of tetrabutyl titanate, isopropyl titanate, titanium dioxide or an inorganic supported titanium catalyst or a combination of at least two thereof.
[0052] Preferably, the aluminum-based catalyst includes aluminum chloride and / or aluminum oxide.
[0053] Preferably, the mass percentage of the catalyst in the copolyester material is 0.3-1.5%, for example, it can be 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, 1.4%, 1.45%, etc.
[0054] Preferably, the light transmittance of the copolyester material is >85% (e.g., 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, etc.), and further preferably >88%.
[0055] Preferably, the oxygen permeability of the copolyester material is less than 30 cm 3 / m 2 ·d·Pa (for example, it can be 29.5cm 3 / m 2 ·d·Pa, 29cm 3 / m 2 ·d·Pa, 28.5cm 3 / m 2 ·d·Pa, 28cm 3 / m 2 ·d·Pa, 27.5cm 3 / m 2 ·d·Pa, 27cm 3 / m 2 ·d·Pa, 26.5cm 3 / m 2 ·d·Pa, 26cm 3 / m 2 ·d·Pa, 25.5cm 3 / m 2 ·d·Pa, 25cm 3 / m 2 ·d·Pa, 24.5cm 3 / m 2 ·d·Pa, 24cm 3 / m 2 ·d·Pa, 23cm 3 / m 2 ·d·Pa, 22cm 3 / m 2 ·d·Pa, 21cm 3 / m 2 ·d·Pa, 20cm 3 / m 2 ·d·Pa, etc.), preferably ≤27cm 3 / m 2 ·d·Pa.
[0056] Preferably, the oxygen permeability of the copolyester material after cooking at 100°C for 60 minutes is less than 40 cm3 / m 2 ·d·Pa (for example, it can be 39.5cm 3 / m 2 ·d·Pa, 39cm 3 / m 2 ·d·Pa, 38.5cm 3 / m 2 ·d·Pa, 38cm 3 / m 2 ·d·Pa, 37.5cm 3 / m 2 ·d·Pa, 37cm 3 / m 2 ·d·Pa, 36.5cm 3 / m 2 ·d·Pa, 36cm 3 / m 2 ·d·Pa, 35.5cm 3 / m 2 ·d·Pa, 35cm 3 / m 2 ·d·Pa, 34.5cm 3 / m 2 ·d·Pa, 34cm 3 / m 2 ·d·Pa, 33cm 3 / m 2 ·d·Pa, 32cm 3 / m 2 ·d·Pa, 31cm 3 / m 2 ·d·Pa, 30cm 3 / m 2 ·d·Pa, 29cm 3 / m 2 ·d·Pa, 28cm 3 / m 2 ·d·Pa, 27cm 3 / m 2 ·d·Pa, 26cm 3 / m 2 ·d·Pa, 25cm 3 / m 2 ·d·Pa, 24cm 3 / m 2 ·d·Pa, etc.), preferably ≤31cm 3 / m 2 ·d·Pa.
[0057] Preferably, the intrinsic viscosity of the copolyester material is 0.5-0.9 dL / g, for example, it may be 0.52 dL / g, 0.55 dL / g, 0.58 dL / g, 0.6 dL / g, 0.62 dL / g, 0.65 dL / g, 0.68 dL / g, 0.7 dL / g, 0.72 dL / g, 0.75 dL / g, 0.78 dL / g, 0.8 dL / g, 0.82 dL / g, 0.85 dL / g, 0.88 dL / g, etc., and more preferably 0.6-0.8 dL / g.
[0058] Preferably, the glass transition temperature of the copolyester material is 140-180°C, for example, it may be 142°C, 145°C, 148°C, 150°C, 152°C, 155°C, 158°C, 160°C, 162°C, 165°C, 168°C, 170°C, 172°C, 175°C, 178°C, etc., and more preferably 150-165°C.
[0059] Preferably, the haze of the copolyester material is 1-5%, for example, it can be 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, etc., and more preferably 2-3.1%.
[0060] In a second aspect, the present invention provides a method for preparing the copolyester material as described in the first aspect, the preparation method comprising the following steps:
[0061] (1) reacting 2,6-naphthalene dicarboxylic acid and / or its esters, other dibasic acids and / or their esters, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and other diols to obtain a reaction product;
[0062] (2) The reaction product is subjected to a polycondensation reaction to obtain the copolyester material.
[0063] Preferably, the 2,6-naphthalene dicarboxylic acid and / or its esterification product comprises 2,6-naphthalene dicarboxylic acid and / or dimethyl 2,6-naphthalene dicarboxylate.
[0064] Preferably, the other dibasic acid and / or its esterification product comprises any one of terephthalic acid, dimethyl terephthalate, diethyl terephthalate, furandicarboxylic acid, 4,4-biphenyldicarboxylic acid, 1,3-isophthalic acid, phthalic acid, dimethyl furandicarboxylate, dimethyl 4,4-biphenyldicarboxylate, dimethyl 1,3-isophthalate or dimethyl phthalate, or a combination of at least two thereof.
[0065] Preferably, the other diols include any one of 1,4-cyclohexanedimethanol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanediol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, dicyclopentanediol, neopentyl glycol or 2-methyl-1,3-propanediol, or a combination of at least two thereof.
[0066] In the present invention, the reaction in step (1) includes esterification reaction and / or transesterification reaction.
[0067] Preferably, the reaction in step (1) is carried out in the presence of a catalyst and / or a composite stabilizer.
[0068] Preferably, the reaction temperature in step (1) is 230-270°C, for example, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, etc.
[0069] Preferably, the reaction time of step (1) is 3-8 h, for example, it can be 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, etc.
[0070] Preferably, the pressure of the reaction in step (1) is 95-105 kPa, for example, it may be 96 kPa, 97 kPa, 98 kPa, 99 kPa, 100 kPa, 101 kPa, 102 kPa, 103 kPa, 104 kPa, etc.
[0071] Preferably, the temperature of the polycondensation reaction is 280-300°C, for example, 282°C, 284°C, 286°C, 288°C, 290°C, 292°C, 294°C, 296°C, 298°C, etc.
[0072] Preferably, the pressure of the polycondensation reaction is 10-100 Pa, for example, it can be 15 Pa, 20 Pa, 25 Pa, 30 Pa, 35 Pa, 40 Pa, 45 Pa, 50 Pa, 55 Pa, 60 Pa, 65 Pa, 70 Pa, 75 Pa, 80 Pa, 85 Pa, 90 Pa, 95 Pa, etc.
[0073] In the present invention, the polycondensation reaction ends when the stirring power reaches a fixed torque value.
[0074] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0075] In a third aspect, the present invention provides a use of the copolyester material as described in the first aspect in food packaging, cosmetic packaging or medical packaging.
[0076] Compared with the prior art, the present invention has the following beneficial effects:
[0077] The copolyester material provided by the present invention has excellent thermal properties, boiling resistance, optical properties and gas barrier properties, wherein the copolyester material has a glass transition temperature of 144-168°C, a light transmittance of 85.5-90.5%, a haze of 2.3-4.2%, and an oxygen permeability of 20-27cm 3 / m 2 ·d·Pa, oxygen permeability after cooking at 100℃ for 60min is 24-35cm 3 / m 2 ·d·Pa, the characteristic viscosity is 0.53-0.73dL / g, suitable for high temperature resistant retort food packaging bags. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] Figure 1 This is the nuclear magnetic resonance hydrogen spectrum of the copolyester in the copolyester material provided in Example 1. DETAILED DESCRIPTION
[0079] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0080] The sources of some components in the embodiments and comparative examples are as follows:
[0081] (1) Dimethyl 2,6-naphthalene dicarboxylate: purchased from Beijing Inokai Technology Co., Ltd.
[0082] (2) Esters of other dibasic acids:
[0083] Dimethyl terephthalate: purchased from Beijing Inokai Technology Co., Ltd.
[0084] Dimethyl 1,3-isophthalate: purchased from Beijing Inokai Technology Co., Ltd.
[0085] Dimethyl furandicarboxylate: purchased from Beijing Inokai Technology Co., Ltd.
[0086] Dimethyl 4,4-biphenyldicarboxylate: purchased from Beijing Inokai Technology Co., Ltd.;
[0087] Dimethyl phthalate: purchased from Beijing Inokai Technology Co., Ltd.
[0088] (3) 2,2,4,4-Tetramethyl-1,3-cyclobutanediol: purchased from Suzhou Yaco Technology Co., Ltd.;
[0089] (4) Other diols: 1,4-cyclohexanedimethanol: purchased from Beijing Inokai Technology Co., Ltd.;
[0090] Neopentyl glycol: purchased from Beijing Inokai Technology Co., Ltd.
[0091] Ethylene glycol: purchased from Beijing Inokai Technology Co., Ltd.;
[0092] 1,2-Cyclohexanediol: purchased from Beijing Inokai Technology Co., Ltd.
[0093] Dicyclopentanediol: purchased from Beijing Inokai Technology Co., Ltd.
[0094] 2-Methyl-1,3-propanediol: purchased from Beijing Inokai Technology Co., Ltd.;
[0095] (5) Dibutyltin oxide: purchased from Anhui Zesheng Technology Co., Ltd.;
[0096] (6) Phosphorus stabilizer
[0097] Antioxidant 168: purchased from Beijing Inokai Technology Co., Ltd.;
[0098] Triphenyl phosphite: purchased from Anhui Zesheng Technology Co., Ltd.;
[0099] Diphenyl phosphate: purchased from Anhui Zesheng Technology Co., Ltd.;
[0100] Ammonium dihydrogen phosphate: purchased from Anhui Zesheng Technology Co., Ltd.;
[0101] Pyrophosphate: purchased from Anhui Zesheng Technology Co., Ltd.;
[0102] (7) Bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate: purchased from Beijing Inokai Technology Co., Ltd.;
[0103] (8) Hindered phenol stabilizers
[0104] Antioxidant 1010: purchased from Beijing Inokai Technology Co., Ltd.;
[0105] 2,4-Dimethyl-6-(1-methylpentadecyl)-phenol: purchased from Beijing Inokai Technology Co., Ltd.;
[0106] N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine: purchased from Beijing Inokai Technology Co., Ltd.;
[0107] 2,6-Di-tert-butyl-4-methylphenol: purchased from Beijing Inokai Technology Co., Ltd.
[0108] (9) N,N'-Dicyclohexylcarbodiimide: purchased from Beijing Inokai Technology Co., Ltd.
[0109] Example 1
[0110] A copolyester material, the components of which include copolyester, dibutyltin oxide, antioxidant 1010 and antioxidant 168;
[0111] The preparation method of the copolyester material comprises the following steps:
[0112] (1) In a four-necked flask equipped with a stirring blade, a condenser, a gas phase port, a feed port and a thermometer, 0.315 mol of dimethyl 2,6-naphthalene dicarboxylate, 0.035 mol of an ester of other dibasic acid (dimethyl terephthalate), 0.186 mol of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 0.207 mol of other diol (1,4-cyclohexanedimethanol), 0.480 g of dibutyltin oxide (catalyst), 0.030 g of antioxidant 1010 and 0.030 g of antioxidant 168 were added; under the protection of high-purity nitrogen, the temperature was raised to 270° C. with stirring, and the reaction was carried out at normal pressure for 5 hours to obtain an ester exchange product;
[0113] (2) The temperature of the ester exchange product is raised to 280° C. under stirring, and the system pressure is gradually reduced to 50 Pa under a constant temperature condition of 280° C. to carry out a polycondensation reaction. The methanol produced by the reaction is removed during the reaction. When the torque of the stirring paddle reaches the target value, the pressure is gradually reduced to normal pressure and the material is discharged to obtain the copolyester material.
[0114] Examples 2-13, Comparative Examples 1-5
[0115] A copolyester material, the raw materials for preparing the copolyester material are shown in Tables 1-3 below, and the preparation method of the copolyester material refers to Example 1.
[0116] Table 1
[0117]
[0118]
[0119] Table 2
[0120]
[0121] Table 3
[0122]
[0123] Performance Testing
[0124] (1) Intrinsic viscosity test: The intrinsic viscosity of the copolyester material was measured in a mixed solution of phenol and tetrachloroethane (mass ratio 3:2) at 25±0.01°C;
[0125] (2) Thermal performance parameter test of copolyester material: nitrogen atmosphere, flow rate of 50 mL / min; during the test, the temperature was first raised to 240°C at 20°C / min, maintained at 240°C for 2 min to remove the thermal history of the copolyester material, then cooled to 30°C at 20°C / min, maintained at 30°C for 2 min, and then raised to 240°C at 20°C / min. The glass transition temperature Tg of the copolyester material was calculated through the second heating curve;
[0126] (3) Copolyester structure characterization: The copolyester material provided in Example 1 was tested using a Bruker nuclear magnetic resonance spectrometer, and the solvent was deuterated chloroform containing tetramethylsilane; the test results are as follows: Figure 1 As shown;
[0127] The testing method for the molar percentage of 2,6-naphthalene dicarboxylic acid residues and the molar percentage of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues in the copolyester material is as follows: 5-10 mg of the copolyester material is placed in a nuclear magnetic resonance tube, 0.55 mL of deuterated chloroform is added, and the mixture is heated and dissolved in a 60°C water bath for 6 hours. After the copolyester material is completely dissolved and a transparent solution is formed, it is tested at room temperature in a Bruker nuclear magnetic resonance instrument.
[0128] For example, the copolyester material provided in Example 1 is tested, and the test results are as follows: Figure 1 As shown by Figure 1 It can be seen that the chemical shifts of the two meta hydrogen atoms of the aromatic ring carbon connected to the carbonyl group in the 2,6-naphthalene dicarboxylic acid residue in the copolyester and the two ortho hydrogen atoms between the aromatic ring carbon connected to the carbonyl group and the meta hydrogen appear at 7.93-8.27 ppm, with a peak area of a. The chemical shifts of the other two ortho hydrogen atoms of the aromatic ring carbon connected to the carbonyl group in the 2,6-naphthalene dicarboxylic acid residue appear at 8.51-8.92 ppm, with a peak area of b. The chemical shifts of the hydrogen atoms on the benzene ring in the terephthalic acid residue appear at 8.09-8. 27ppm, peak area c, c = a-2b; the hydrogen atoms of CH in the 2,2,4,4-tetramethyl-1,3-cyclobutanediol residue appear at 4.6-5.0ppm, with a peak area d; the hydrogen atoms of the two CH2 connected to the cyclohexane structure of the 1,4-cyclohexanedimethanol residue appear at 4.12-4.48ppm, with a peak area e; the calculation formula for the molar percentage of the 2,6-naphthalene dicarboxylic acid residue and the 2,2,4,4-tetramethyl-1,3-cyclobutanediol residue is as follows:
[0129]
[0130]
[0131] (4) Optical properties: The copolyester material was injection molded into a sample with a length of 8 cm × width of 5 cm × thickness of 1.7 mm using an injection molding machine (Haitian Plastic Machinery Group Co., Ltd., MA250T). The transmittance and haze of the copolyester material were tested using a transmittance / haze tester (Shanghai Precision Instrument Co., Ltd., WGT-S);
[0132] (5) Gas barrier performance test: The copolyester material was made into a sheet with a thickness of 0.6 mm using a flat vulcanizer (Qingdao Jinjiuzhou Rubber Machinery Co., Ltd.), and the oxygen permeation rate was measured using a differential pressure method and a gas permeability tester (Jinan Sike Testing Technology Co., Ltd., GTR-7006) at 25°C and 0% RH. The differential pressure was 0.1 MPa.
[0133] (6) Boiling resistance test: The parallel samples for gas barrier performance test were placed in boiling water at 100°C and boiled for 60 min. The oxygen permeation rate after boiling was measured using a pressure difference method and a gas permeability tester (Jinan Sike Testing Technology Co., Ltd., GTR-7006) at 25°C and 0% RH. The pressure difference was 0.1 MPa.
[0134] The copolyester materials provided in Examples 1-13 and Comparative Examples 1-5 and the copolyesters contained therein were tested according to the above method. The test results are shown in Tables 4-6 below:
[0135] Table 4
[0136]
[0137] Table 5
[0138]
[0139] Table 6
[0140]
[0141] The test data in the table show that the copolyester material provided by the present invention has excellent thermal properties, cooking resistance, optical properties and gas barrier properties, and its glass transition temperature is 144-168°C, the intrinsic viscosity is 0.53-0.73dL / g, the light transmittance is 85.5-90.5%, the haze is 2.3-4.2%, and the oxygen permeability before cooking is 20-27cm 3 / m 2 ·d·Pa, oxygen permeability after cooking is 24-35cm 3 / m 2 ·d·Pa.
[0142] In Example 7, the molar percentage of 2,6-naphthalene dicarboxylic acid residues in the molecular structure of the copolyester decreased, and in Example 8, the molar percentage of 2,2,4,4-tetramethyl-1,3-cyclobutanediol in the molecular structure of the copolyester decreased, and the glass transition temperature of the copolyester materials decreased. In Example 9, the molar percentage of low-activity 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues in the molecular structure of the copolyester increased, and the intrinsic viscosity of the copolyester decreased.
[0143] It can be seen from Examples 10 and 11 that when the content of the hindered phenol stabilizer or the phosphorus stabilizer in the composite stabilizer is low, the light transmittance of the copolyester material decreases and the haze increases. It can be seen from Examples 12 and 13 that when a non-phosphorus stabilizer is used instead of a phosphorus stabilizer, or a non-hindered phenol stabilizer is used instead of a hindered phenol stabilizer, the intrinsic viscosity and light transmittance of the copolyester material decrease, and the haze increases. When the phosphorus stabilizer and the hindered phenol stabilizer are used as a composite stabilizer, the technical effect is better.
[0144] In the molecular structure of the copolyester of Comparative Example 1, the molar percentage of 2,6-naphthalene dicarboxylic acid residues is too small, the glass transition temperature is reduced, the retort resistance is deteriorated, and the gas barrier property is deteriorated. In the molecular structure of the copolyester of Comparative Example 2, there is no 2,6-naphthalene dicarboxylic acid residue in the copolyester, the glass transition temperature of the copolyester material is significantly reduced, the retort resistance is deteriorated, and the gas barrier property is deteriorated.
[0145] It can be seen from Comparative Example 3 that the molar percentage of the 2,6-naphthalene dicarboxylic acid residue is too high, the intrinsic viscosity of the copolyester material is reduced, and thus the copolyester material has no use value.
[0146] It can be seen from Comparative Example 4 that the molar percentage of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues is too high, the intrinsic viscosity of the copolyester material decreases, the gas barrier property deteriorates, the boiling resistance decreases, and the haze increases.
[0147] It can be seen from Comparative Example 5 that the molar percentage of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues is too low, the glass transition temperature of the copolyester material is significantly reduced, and the boiling resistance is significantly reduced.
[0148] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the copolyester material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A copolyester material, characterized in that: The components of the copolyester material include copolyester; the copolyester contains dibasic acid residues and diol residues; The dibasic acid residue comprises: (a1) 70-98 mol % of 2,6-naphthalene dicarboxylic acid residues, based on the total molar amount of (a1) and (a2); (a2) 2-30 mol % of other dibasic acid residues based on the total molar amount of (a1) and (a2); wherein the sum of the molar percentages of residues (a1) and (a2) is 100%; The diol residue comprises: (b1) 10 to 60 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, based on the total molar amount of (b1) and (b2); (b2) 40 to 90 mol % of other diol residues, based on the total molar amount of (b1) and (b2); The total molar percentage of the residues (b1) and (b2) is 100%.
2. The copolyester material according to claim 1, characterized in that: The other dibasic acid residues include any one of terephthalic acid residues, furandicarboxylic acid residues, 4,4-biphenyldicarboxylic acid residues, 1,3-isophthalic acid residues or phthalic acid residues, or a combination of at least two thereof.
3. The copolyester material according to claim 1, characterized in that: The dibasic acid residue comprises: (a1) 75-95 mol % of 2,6-naphthalene dicarboxylic acid residues, based on the total molar amount of (a1) and (a2); (a2) 5-25 mol % of other dibasic acid residues based on the total molar amount of (a1) and (a2); The total molar percentage of the residues (a1) and (a2) is 100%.
4. The copolyester material according to claim 1, characterized in that: The other diol residues include any one of 1,4-cyclohexanedimethanol residues, 1,4-cyclohexanediol residues, 1,2-cyclohexanedimethanol residues, 1,3-cyclohexanediol residues, 1,2-cyclohexanediol residues, 1,3-cyclohexanediol residues, ethylene glycol residues, 1,3-propylene glycol residues, 1,4-butanediol residues, dicyclopentanediol residues, neopentyl glycol residues or 2-methyl-1,3-propanediol residues, or a combination of at least two thereof; Preferably, the diol residue comprises: (b1) 25 to 50 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, based on the total molar amount of (b1) and (b2); (b2) 50-75 mol % of other diol residues, based on the total molar amount of (b1) and (b2); The total molar percentage of the residues (b1) and (b2) is 100%.
5. The copolyester material according to claim 1, characterized in that: The components of the copolyester material also include a composite stabilizer; Preferably, the composite stabilizer includes a phosphorus stabilizer and a hindered phenol stabilizer; Preferably, the phosphorus stabilizer includes any one or a combination of at least two of diphenyl phosphate, triphenyl phosphite, trimethyl phosphate, dimethyl phosphate, triphenyl phosphate, diphenyl phosphite, ammonium phosphite, diammonium phosphate, phosphorous acid, hypophosphorous acid, pyrophosphoric acid, tris(2,4-di-tert-butylphenyl)phosphite or ammonium phosphate; Preferably, the mass percentage of the phosphorus stabilizer in the composite stabilizer is 10-90%, more preferably 45-75%; Preferably, the hindered phenol stabilizer includes any one or a combination of at least two of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, 2,4-dimethyl-6-(1-methylpentadecyl)-phenol, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine or 2,6-di-tert-butyl-4-methylphenol; Preferably, the mass percentage of the hindered phenol stabilizer in the composite stabilizer is 10-90%, more preferably 25-55%; Preferably, the mass percentage of the composite stabilizer in the copolyester material is 0.01-1%.
6. The copolyester material according to claim 1, characterized in that: The components of the copolyester material also include a catalyst; Preferably, the catalyst comprises any one or a combination of at least two of a tin-based catalyst, an antimony-based catalyst, a germanium-based catalyst, a titanium-based catalyst or an aluminum-based catalyst; Preferably, the tin-based catalyst includes any one of dibutyltin oxide, stannous isooctanoate, monobutyltin triisooctanoate or dioctyltin oxide, or a combination of at least two thereof; Preferably, the antimony-based catalyst includes any one of antimony acetate, antimony trioxide, ethylene glycol antimony or polyethylene glycol antimony, or a combination of at least two thereof; Preferably, the germanium-based catalyst comprises germanium dioxide and / or germanium oxide; Preferably, the titanium-based catalyst includes any one or a combination of at least two of tetrabutyl titanate, isopropyl titanate, titanium dioxide or an inorganic supported titanium catalyst; Preferably, the aluminum-based catalyst comprises aluminum chloride and / or aluminum oxide; Preferably, the mass percentage of the catalyst in the copolyester material is 0.3-1.5%.
7. The copolyester material according to claim 1, characterized in that: The light transmittance of the copolyester material is >85%, and more preferably >88%; Preferably, the oxygen permeability of the copolyester material is less than 30 cm 3 / m 2 ·d·Pa, preferably ≤27cm 3 / m 2 ·d·Pa; Preferably, the oxygen permeability of the copolyester material after cooking at 100°C for 60 minutes is less than 40 cm 3 / m 2 ·d·Pa, preferably ≤31cm 3 / m 2 ·d·Pa; Preferably, the intrinsic viscosity of the copolyester material is 0.5-0.9 dL / g, more preferably 0.6-0.8 dL / g; Preferably, the glass transition temperature of the copolyester material is 140-180°C, more preferably 150-165°C; Preferably, the haze of the copolyester material is 1-5%, more preferably 2-3.1%.
8. A method for preparing a copolyester material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) reacting 2,6-naphthalene dicarboxylic acid and / or its esters, other dibasic acids and / or their esters, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and other diols to obtain a reaction product; (2) The reaction product is subjected to a polycondensation reaction to obtain the copolyester material.
9. The preparation method according to claim 8, characterized in that: The 2,6-naphthalene dicarboxylic acid and / or its esterification product include 2,6-naphthalene dicarboxylic acid and / or 2,6-naphthalene dicarboxylic acid dimethyl ester; Preferably, the other dibasic acid and / or its esterification product comprises any one or a combination of at least two of terephthalic acid, dimethyl terephthalate, diethyl terephthalate, furandicarboxylic acid, 4,4-biphenyldicarboxylic acid, 1,3-isophthalic acid, phthalic acid, dimethyl furandicarboxylate, dimethyl 4,4-biphenyldicarboxylate, dimethyl 1,3-isophthalate or dimethyl phthalate; Preferably, the other diols include any one or a combination of at least two of 1,4-cyclohexanedimethanol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanediol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, dicyclopentanediol, neopentyl glycol or 2-methyl-1,3-propylene glycol; Preferably, the reaction in step (1) is carried out in the presence of a catalyst and / or a composite stabilizer; Preferably, the reaction temperature in step (1) is 230-270°C; Preferably, the reaction time in step (1) is 3-8h; Preferably, the reaction pressure in step (1) is 95-105 kPa; Preferably, the temperature of the polycondensation reaction is 280-300°C; Preferably, the pressure of the polycondensation reaction is 10-100 Pa.
10. Use of the copolyester material according to any one of claims 1 to 7 in food packaging, cosmetic packaging or medical packaging.
Citation Information
Patent Citations
High-transparency and high-heat-resistance copolyester resin and preparation method thereof
CN113321796A
Copolyester and production method thereof
JP2010031175A
Process for the preparation of copolyesters based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 1,4-cyclohexanedimethanol
US20070276065A1